Advances of Magnetic Nanohydrometallurgy Using Superparamagnetic Nanomaterials as Rare Earth Ions Adsorbents: A Grand Opportunity for Sustainable Rare Earth Recovery - Venegas-Yazigi, D; Venegas-Yazigi, D (Elsevier B.V., 2022)
Rare earth elements (REEs) are among the most important raw materials in developing new high-tech devices. There are many ways to recover REE ions from diverse sources. A new emerging sustainable technology is Magnetic Nanohydrometallurgy (MNHM). It combines nanotechnology with the hydrometallurgy process as the adsorption. It is one of the most promising due to its simplicity, high efficiency, low cost, environmentally friendly, and excellent efficiency for recovering metal ions. The MNHM uses functionalized-magnetic nano adsorbents (MNAs) with specific complexing agents to extract, concentrate, and separate metal ions as REEs from diluted leaching solutions. The MNAs have the main advantage possess superparamagnetism, easing their separation from aqueous media by an external magnetic field (magnetic separation). This paper compiles the recent results published in the literature on the current synthesis methods, types of assembly, and surface modification procedures for MNAs. Furthermore, the REEs adsorption behavior onto MNAs is discussed in detail, as the factors affecting adsorption (pH, adsorbent dose, ionic strength, contact time, temperature, REEs concentration). The MNAs generally showed high REEs’ adsorption capacity, fast removal rates, excellent selectivity, and great reusability power. The adsorption process, which mostly follows the Langmuir isotherm, and the pseudo-second-order kinetic model, is typically endothermic, decreasing randomness and being spontaneous. The dominant adsorption mechanisms were surface complexation and electrostatic interaction. The MNHM is a promising cleaner technology compared to other more conventional technologies because it allows multiple reuses of MNAs, and eliminates consuming organic solvent. Most MNAs used in the REEs adsorption are environmentally friendly. © 2022 Elsevier B.V.
Keywords: Rare earth elements; Magnetic nanohydrometallurgy; Functionalized-magnetic nano adsorbent; Magnetic separation; Adsorption mechanisms; Desorption